From historical memory of World War II to the capital of historical memory or how the culture of memory is transforming in the consciousness of Russian students - Vishnevsky, Yuri; Pevnaya, Maria; Kulminskaia, Alina; Vučković, Branislava (Sociološki pregled, 2026)
The article is devoted to the study of the culture of memory in Russia. The article presents the results of a sociological study of the dynamics of historical memory of World War II in the minds of Russian students. It is based on the monitoring data of the Russian Society of Sociologists. It was conducted from 2005 to 2025. The 2025 sample is 19,236 students from 82 universities. The article shows that understanding the memory of the Victory in this war as capital gives it social meaning and significance. Such an interpretation forms a sense of usefulness in its subject, actualizing the experience of the past and expanding opportunities in the present and future, preserving the culture of memory of the nation. The article shows the inconsistency of the patriotic perception of the history of the war by Russian students - an increase in interest in these events and the preservation of the “deformation of memory” laid down in the 1990s.